The application of DNA molecular markers in the study of Codonopsis species genetic variation, a review - Yang, Mingjun; Abdalrahman, Hosham; Sonia, Uwimbabazi; Mohammed, Alaa I; Vestine, Uwitugabiye; Wang, Minggang; Ebadi, Abdol Ghaffar; Toughani, Mohsen (Cellular and Molecular Biology, 2020)
Codonopsis genus is comprised of species that are perennial plants primarily distributed across all east, southeast, and Central Asia. The most famous species of Codonopsis are C. tangshen, C. lanceolate, and C. pilosula. The records showed that they have a long story usage as traditional Chinese medicines, as they were alleged to be able to intensify the spleen and the lung as well as enriching blood and engendering liquid. Certain species have a culinary value in southern China and Southeast Asia, where they are considered as tea, wine, soup, plaster, and porridge. Codonopsis species were shown to be of great importance in medicine, due to their broad biological activity. Therefore, a clear understanding of their genetic diversity is needed. Adequate distinctions and descriptions of those species are necessary to preserve plant reservoir, investigations of genes associated with desirable traits, and understanding of evolutionary relationships. Subsequently, various molecular marker techniques such as Random Amplified Polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP), Simple Sequence Repeats (SSR), and Inter Simple Sequence Repeat (ISSR), Single Nucleotide Polymorphism (SNP), internal transcribed spacer (ITS), and Sequence-Characterized Amplified Region (SCAR) have been improved to provide detailed informations about genomes, that historically were not possible to obtain based on only phenotypic methods. This review represents the usage of DNA molecular markers for molecular diversity analysis of medically important species belonging to the genus Codonopsis.